2022
DOI: 10.3390/cancers14235792
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Guide to Peptide Receptor Radionuclide Therapy with 177Lu-DOTATATE in Neuroendocrine Tumor Patients

Abstract: Peptide receptor radionuclide therapy (PRRT) with [177Lu]Lu-[DOTA0,Tyr3]-octreotate (177Lu-DOTATATE) has become an established second- or third-line treatment option for patients with somatostatin receptor (SSTR)-positive advanced well-differentiated gastroenteropancreatic (GEP) neuroendocrine tumors (NETs). Clinical evidence of the efficacy of PRRT in tumor control has been proven and lower risks of disease progression or death are seen combined with an improved quality of life. When appropriate patient selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 121 publications
0
13
0
Order By: Relevance
“…It remains unclear if, and how long SSA should be continued after PRRT as a maintenance therapy. Opinions favoring the early consideration of PRRT are accumulating (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear if, and how long SSA should be continued after PRRT as a maintenance therapy. Opinions favoring the early consideration of PRRT are accumulating (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…40 Patients who are at risk for severe hematological toxicity include those with "decreased renal function, pre-existent cytopenias, extensive tumor mass, age over 70, extensive bone metastases (due to the risk of persistent cytopenia), and pre-treatment with myelotoxic chemotherapy." 41 Treatment with PRRT should not necessarily be withheld for patients with these characteristics, but they are factors to be considered as part of the MDT discussion. Everolimus is recommended as a second- or later-line option for patients who are SSTR-negative or may not be candidates for PRRT.…”
Section: Recommendationsmentioning
confidence: 99%
“…F or more than 2 decades, radiolabeled somatostatin receptor treatment (peptide receptor radionuclide therapy [PRRT]) has been used as a well-established treatment option for patients with low-grade neuroendocrine tumors (NETs). 1 Over time, the radionuclide was changed iteratively, with 177 Lu currently being the preferential radionuclide for PRRT in patients with NET. [1][2][3][4][5][6] The prospective phase 3 NETTER1 trial had crucial impact on the therapy stratification for patients with metastasized G1 (Ki67 <3%) and G2 (Ki67 3% to 20%) midgut NETs.…”
mentioning
confidence: 99%
“…1 Over time, the radionuclide was changed iteratively, with 177 Lu currently being the preferential radionuclide for PRRT in patients with NET. [1][2][3][4][5][6] The prospective phase 3 NETTER1 trial had crucial impact on the therapy stratification for patients with metastasized G1 (Ki67 <3%) and G2 (Ki67 3% to 20%) midgut NETs. In this study, patients receiving 177 Lu-DOTATATE showed significantly better progression-free survival (PFS) and overall survival (OS) rates compared with patients in the octreotide-treated control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation